PERILAKU PENCARIAN INFORMASI WANITA YANG TINGGAL DI DAERAH KUMUH DI KAMPUNG PONCOL, JAKARTA SELATAN, INDONESIA - Abdi, Fauzan; Rachman, Margareta Aulia (Universitas Pendidikan Indonesia, 2017)
Abstract. This research identifies the information seeking behavior of women who reside in the slum area of Kampung Poncol, Jakarta, Indonesia in the fulfillment of the triple role; those are reproductive, productive, and social. A qualitative approach with phenomenology method is used in this research while the data are collected by non-participant observation and in-depth interview with six participants. The results of this research show that the steps of information seeking behavior of those women are the initiation, selection, formulation, collection, and presentation; while the exploration step does not appear at all. Based on the role of reproduction needed by the informants in relation to their role as housewives, the information needed by the women are about the price of basic commodities, family healthcare and well-being, children education, as well as information about the flood. On the productive role, the information needed are vary among the informants depends on their occupations. While for the social role, the information needed by the informants are related to personal health, fashion, entertainment, and politics. The primary source of information is informal source those are relatives and neighbors.